The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1590/s0074-02761998000600015
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Taxonomy of Old World Phlebotominae (Diptera: Psychodidae): 1. Considerations of Morphological Characters in the Genus Phlebotomus Rondani & Berté 1840

Abstract: Numerical analyses (correspondence analysis, ascending hierarchical classification, cladistic approach)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 7 publications
3
17
0
1
Order By: Relevance
“…Within the Phlebotominae of the Old World, the genus Sergentomyia França & Parrot, 1920 appears to be a catch fall group, including all the Old World species excluded from all other genera ( Phlebotomus , Idiophlebotomus , Chinius , Spelaeophlebotomus , Grassomyia , Parviden s, Spelaeomyia and Demeillonius ) [24], [25], [32]. Species of the genus Sergentomyia share the following characters: a mesanepisternum without setae, abdominal tergites 2–6 carrying usually all or most recumbent hairs, an usual 1/III–XV antennal formula in the males and 2/III–XV in the females with some exceptions, a cibarium with an armature of teeth and/or denticled more developed in females than in males (beyond exceptions), a single paramere, a style with four terminal spines (or often 2 terminal and 2 subterminal) and an accessory spine.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Phlebotominae of the Old World, the genus Sergentomyia França & Parrot, 1920 appears to be a catch fall group, including all the Old World species excluded from all other genera ( Phlebotomus , Idiophlebotomus , Chinius , Spelaeophlebotomus , Grassomyia , Parviden s, Spelaeomyia and Demeillonius ) [24], [25], [32]. Species of the genus Sergentomyia share the following characters: a mesanepisternum without setae, abdominal tergites 2–6 carrying usually all or most recumbent hairs, an usual 1/III–XV antennal formula in the males and 2/III–XV in the females with some exceptions, a cibarium with an armature of teeth and/or denticled more developed in females than in males (beyond exceptions), a single paramere, a style with four terminal spines (or often 2 terminal and 2 subterminal) and an accessory spine.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was recently found that species from other genera could also play a role in leishmaniases transmission in Theodor, 1948, and (Kasaulius) Lewis, 1982. However, Rispail andLéger (1998a) thought the subgenus (Anaphlebotomus) is artificial, because it includes two lineages. New species from Madagascar belonging to this group were recently described (Depaquit et al 2002, Randrianambinintsoa et al 2013, suggesting this subgenus needs to be revised.…”
Section: Discussionmentioning
confidence: 99%
“…The renewed interest in the classification of Phlebotominae on morphological characters can contribute to this (Galati 1995, Rispail & Léger 1998a but analyses of molecular data will probably help to resolve both taxonomy and phylogeny less ambiguously than has been possible by morphology alone. We suggest that inclusion of L. derelicta in such analyses would be of particular interest.…”
Section: Discussionmentioning
confidence: 99%